Catalytic Growth of Graphitic Carbon‐Coated Silicon as High‐Performance Anodes for Lithium Storage. Issue 10 (8th August 2019) - Shi, Minyuan; Nie, Ping; Fu, Ruirui; Fang, Shan; Li, Zihan; Dou, Hui; Zhang, Xiaogang
Abstract : Although silicon is considered as one of the most promising anode materials in next‐generation lithium‐ion batteries, large volumetric expansion during cycling hampers its practical application. The fabrication of silicon/carbon composites is an effective way to improve electrical conductivity and inhibit electroactive material delaminating from the current collector. Herein, a graphitic carbon‐coated porous silicon nanospheres (p‐SiNSs@C) composite is prepared through a chemical vapor deposition (CVD) technique by using the magnesiothermic reduction by‐product MgO as a template and catalyst. With the template of in situ generation of MgO, the p‐SiNSs@C material is obtained in a very short time. Due to the graphitic carbon shell and porous structure inside the silicon nanospheres, the obtained p‐SiNSs@C, with 8 min carbon growing time (p‐SiNSs@C‐2), deliver a high initial reversible capacity of 2220 mAh g −1 at 0.1 A g −1 and respectable rate capability. Furthermore, the p‐SiNSs@C‐2//LiCoO2 Li‐ion full cell displays a high energy density of ≈409 Wh kg −1 and good cycling performance. The high performance of the p‐SiNSs@C‐2 composite can be attributed to the synergistic effect of nanoscale‐sized Si, porous structure, and stable carbon shell. Abstract : Monodisperse porous silicon is made by magnesiothermic reduction. With the magnesiothermic by‐product MgO as catalyst and template, high graphitic carbon can grow through a chemical vapor deposition (CVD) method. The as‐made graphitic carbon‐coated porous silicon nanospheres (p‐SiNSs@C) composite has a high performance for lithium storage.